SOX and the Transition from Apartheid to Democracy: South African Auditing Developments through the Lens of Modernity Theory. (15th May 2014) - Maroun, Warren; Coldwell, David; Segal, Milton
<x xml:space="preserve">Abstract</x> This paper uses South Africa as an example to explore how crises of trust – stemming from the legacy of Apartheid, local and international corporate failures and the changing regulatory framework in the United States – have contributed to shaping aspects of South African corporate governance. Using Giddens' theory of modernity, the research considers how the country's racist past and recent corporate scandals have converged to shape South Africa's corporate governance landscape. In turn, mechanisms of modernity explain why South Africa has developed a highly sophisticated system of corporate governance.